Vibration Analysis of Bidirectional Functionally Graded Porous Plates Using MITC3+ - Hoang, Nhan Thinh; Ho, Thuan N.-T.; Pham, Quoc Hoa; Van, Tran The (International Journal of Membrane Science and Technology, 2023)
The article presents the vibration behavior of bidirectional functionally graded (BDFG) porous plates using the new triangular 3-node element (a cubic bubble function for the interpolation of the rotations to enrich the bending displacements) which is called the MITC3+ element. The BDFG porous plates have material properties varying in two directions with even and uneven porosity distribution. Based on Hamilton’s principle, the motion equations for BDFG plates are derived. Then, some examples are performed to verify the accuracy and reliability of the proposed method. Finally, the new numerical results on the free vibration response of BDFG porous plates are provided.